Sex Dolls in Islamic Thought: A Qur’anic and Maqasidic Analysis of Sexuality and Tamatsil - Wicaksono, Muhammad Pradipa; Hakim, Lukmanul; Saifullah, Saifullah; Nixson, Nixson; Putra, Masyhuri (TAFSE: Journal of Qur'anic Studies, 2024)
The increasing use of sex dolls raises ethical, social, and religious concerns, particularly in Islamic discourse. While Islamic scholarship has extensively discussed sexuality and statues (tamatsil), there remains a research gap in analyzing their intersection within modern technology. This study examines the permissibility of sex dolls within Islamic ethics and law by integrating Qur’anic interpretation and Maqasid al-Shariah. A qualitative hermeneutical and thematic (tafsir maudhu’i) approach is employed to analyze Surah Al-Ma'arij (70:29-31), Surah Saba’ (34:13), and Surah Al-Anbiya' (21:52). Classical and contemporary exegeses, along with fatwas from Dar al-Ifta' Egypt, Saudi Arabia, and Indonesia, provide legal insights. Findings indicate that sex dolls contradict Islamic ethical principles, particularly hifz al-‘ird (preserving dignity), hifz an-nasl (preserving lineage), and hifz al-aql (preserving intellect). Fatwas classify sex dolls as haram due to their potential to normalize unethical behavior and disrupt marital relationships.